Innovation management in research and industry - Davim, J. Paulo; Machado, Carolina, 1965- (EBL-Schweitzer., 2015)
As a consequence of social, technological, political and economic changes, the field of organizations management and engineering becomes highly complex, calling for more effective strategies. In this book, the authors discuss innovative technological resources and their implications on organizational policies, strategies, and flexibility, as well as on sustainable management.